The Development of Small and Medium Enterprises - Their Impact on the Growth of Employment in Kosovo - Terziu, Hysni; Lushi, Isuf (European Journal of Economics and Business Studies, 2016)
The development of small and medium enterprises (SME) at a satisfied level can be achieved only through the application of knowledge and best practices that are developed at private sector, considering as their main derivation - the creation of new work places. The purpose of this paper is that even in our theory and practice to be provided modern concepts regarding the management of small and medium enterprises and regarding the business decision making. Small and medium enterprises can be considered as engines for the creation of new working places, in other words, can be considered as incubators for innovation and entrepreneurship. But in many poor countries, small and medium enterprises are not considered as the main players in the local ecosystem, which makes many of them operating outside the formal legal system and which phenomena results in the increase of informality and in the decrease of productivity. In addition, the condition becomes harder as they lack the funding and the long-term capital which on the other hand are the basis for the creation and function of companies. The development of SMEs is considered as the basic generator of economic growth. This development should be based on the advantages which should be further developed and on the obstacles and weaknesses, which, through strategies and means of economic policy, must be overcome and revitalized. Based on our studies, in the overall context of this work can be conducted the structuring of SMEs and the process of making business decisions in Kosovo. The focus of the analysis in this paper is the creation of friendly conditions for the development of small and medium enterprises towards employment policies and structural reforms, institutional market economy, generating of new work places. The necessity of these actions lays on the fact that in Kosovo exists a very large army of unemployed youth. The world today is undergoing through a global financial crisis which had started in the United States in 2008 and which has spread all around the globe. It can be said that this global financial crisis has been the longest that this world has recognized. For this reason, to the government of any country is added one more task, which is even more difficult, that through its policies to do the impossible in order to overcome this crisis and to send the respective country towards economic development, more specifically towards the development of the small and medium enterprise which in turn will have an impact on the decrease of unemployment. In addition, the purpose of this study would be to identify the current situation of small and medium enterprises, their structuring and their components in Kosovo.